Economic Growth versus Covid-19 Pandemic in East Java Province: Estimating The Role of Internet - Siswantoro Siswantoro (Universitas Brawijaya, 2022)
During the COVID-19 Pandemic in Indonesia, the government implemented a policy of work-from-home which made the role of the internet increasingly urgent to keep the economy running amidst the pandemic. This paper aims to investigate how the role of internet infrastructure in influencing economic growth during the 2-year pandemic using the panel regression. To obtain accurate results, other variables that can affect economic growth such as the rate of spread of positive COVID-19 cases, poverty, and unemployment are also investigated. Empirical data of 38 districts and cities in East Java Province in 2020-2021 were evaluated to investigate the effect of internet infrastructure on economic growth during the pandemic.The main research results show that internet infrastructure has a positive and significant impact on economic growth in East Java during 2 years of the pandemic. The regression estimation results show that an increase of 1% in areas with 4G internet access in East Java can result in economic growth of 0.07558% during the pandemic or 10 times higher than before the pandemic. Other findings prove that the spread of the rate of positive COVID-19 cases has a significant effect in reducing economic growth by 0.000549 in East Java during the pandemic. Meanwhile, another variable that affects economic growth during the pandemic in East Java is unemployment, while poverty does not show a significant effect.